Antibacterial Activity Test of an Ethanol Extract Toner Formulation from Water Apple Leaves (Syzygium aqueum) Against Propionibacterium acnes - Darojatun Ni'mah; Yani’ Qoriati; Atika Nirmala (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Acne vulgaris is an inflammatory condition of the pilosebaceous unit, one of the contributing causes of which namely the bacterium Propionibacterium acnes. Long-term utilization of synthetic antibacterial agents may result in bacterial antibiotic resistance; therefore, alternative therapies based on natural ingredients are needed. Leaves from the water apple plant (Syzygium aqueum). Contain active compounds which consists of flavonoids, tannins, saponins, and alkaloids, which possess bacterial inhibition activity and can be formulated into skincare products such as toners. Toner refers to a liquid skincare preparation that is applied to assist in cleansing the skin from residual impurities, balance skin pH, control excess oil, and help manage acne problems. Aim: The purpose of this study was to evaluate the physical characteristics and antibacterial effect of an ethanolic extract toner formulation derived from water apple leaves active against Propionibacterium acnes. Method: Inhibitory power test research method (agar diffusion – disk) with four variations of extract concentration, namely F0 (0%), F1 (1%), F2 (3%), and F3 (5%). Extraction was carried out by maceration using 96% ethanol. The toner To ensure quality, the prepared toner samples underwent several physical assessments, including observation of appearance, consistency, pH value, moisture content, andflow properties. Antibacterial activity was assessed using the agar diffusion method with paper discs. Results: The results showed that the water apple leaf extract toner formulations met the quality requirements in accordance with the Indonesian National Standard (SNI) for topical preparations, as indicated by acceptable organoleptic properties, homogeneity, pH, moisture content, and viscosity. Furthermore, the antibacterial activity test demonstrated that the ethanol extract toner formulation F3 at a concentration of 5% exhibited the strongest inhibitory effect against Propionibacterium acnes, with an average inhibition zone diameter of 15.03 mm. Conclusion: The ethanol extract toner preparation of guava leaves meets physical quality standards according to SNI and has fairly high effectiveness as an antibacterial agent in inhibiting the growth of bacteria that cause acne.